Endoscopic Third Ventriculostomy before Posterior Fossa Tumor Surgery in Adult Patients - Marx, Sascha; El Damaty, Ahmed; Manwaring, Jotham; El Refaee, Ehab; Fleck, Steffen; Fritsch, Michael; Gaab, Michael R.; Schroeder, H.W.S.; Baldauf, Jörg (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Objective Obstructive hydrocephalus in patients with posterior fossa tumors is frequently seen. Treatment options include immediate tumor removal or prior cerebrospinal fluid (CSF) diversion procedures. The necessity and feasibility of an ETV in these situations has not yet been proven in adult patients.Methods We retrospectively reviewed our prospectively maintained database for ETVs before surgery of posterior fossa tumors in adults. The primary focus of data analyses was the question of whether the ETV was suitable to treat the acute situation of hydrocephalus without an increased rate of complications due to the special anatomical situation with a posterior fossa tumor. We also analyzed whether any further CSF diverting procedures were necessary.Results A total of 40 adult patients who underwent an ETV before posterior fossa tumor surgery were analyzed. Overall, 33 patients (82.5%) had clinical signs of hydrocephalus, and all of them improved in their clinical course after ETV. Seven patients (17.5%) did not demonstrate clinical signs of hydrocephalus, but ETV was performed with prophylactic or palliative intent in six patients and one patient, respectively. No complications were observed due to ETV itself. No permanent shunting procedure was necessary in a mean follow-up of 76.5 months. Early additional CSF diverting procedures (redo ETV, external ventricular drain) were performed in five patients (12.5%).Conclusion The present series confirms the feasibility and safety of ETV before posterior fossa tumor surgery in adult patients. If patients had symptomatic hydrocephalus before tumor surgery, an ETV can be performed, followed by early elective tumor surgery. A prophylactic ETV in asymptomatic patients is not advised. Early elective tumor surgery should be performed in these patients.
Keywords: endoscopic third ventriculostomy; posterior fossa tumor; management of hydrocephalus